Adsorption of pure and predicted binary (CO2:CH4) mixtures on 13X-Zeolite: Equilibrium and kinetic properties at offshore conditions - Abdul Kareem, F.A. (Elsevier B.V., 2018)
The growth in energy demand for natural gas has led to the exploration of sub-quality natural gas reserves with high CO2 content up to 80 at the offshore condition with temperature and pressure approximately 50 Â°C and 70 bar. In this work, a gravimetric technique is used to study CO2 and CH4 adsorptions on 13Ã zeolites at 50 Â°C and up to 70 bar pressure as an adequate range for offshore operations. 13Ã zeolite shows high CO2 adsorption capacity with 5.226 mmol/g at 50 Â°C compared to 4.29 mmol/g at 70 Â°C. The same trend is noticed for CH4 adsorption on both temperatures. Four equilibrium isotherm models are used to analyze the adsorption data i.e. Langmuir, Freundlich, Toth, and Sips. Virial isotherm model is applied on the experimental data to illustrate the isosteric heat of adsorption and it shows an excellent agreement with R2 = 0.998 for 13Ã MSZ. Henry's law constant is estimated utilizing Virial coefficients, which shows higher molar selectivity ratio for CO2 on 13Ã with Î± Ë 3.957 at 50 Â°C as compared to the Î± Ë 3.736 at 70 Â°C. Extended Langmuir (EL) Model and Multisite Langmuir (MSL) models are applied for 30:70, 50:50, and 70:30 CO2:CH4 binary mixtures. The outcomes of MSL exhibit high agreement with the quadrupole and polarizability of the single component and the mixtures. The kinetic rate constant is estimated according to the applied LDF model at higher operational regions. The 13Ã MSZ shows feasibly good isosteric heat of adsorption, which might refer to the large surface area and pore volume that can accommodate CO2 at higher speed and quantity at offshore conditions. Â© 2018 Elsevier Inc.